2016
DOI: 10.1016/j.toxrep.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity determinants of multi-walled carbon nanotubes: The relationship between functionalization and agglomeration

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 69 publications
1
107
0
2
Order By: Relevance
“…A possible explanation is that increasing the diameter increases the bioactivity and induces significant immune response, which is consistent with previous studies showing that longer MWCNT are more bioactive. 43 Studies have also shown that degree of agglomeration, 26,44,45 charge, 46 surface chemical modification, 47 and metal contaminants 48 could affect CNT toxicity in vivo or in vitro. Comparing with f-MWCNT, more inflammation occurred in the p-MWCNTs.…”
Section: Physicochemical Characteristic Dependency Of Effects/relatiomentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that increasing the diameter increases the bioactivity and induces significant immune response, which is consistent with previous studies showing that longer MWCNT are more bioactive. 43 Studies have also shown that degree of agglomeration, 26,44,45 charge, 46 surface chemical modification, 47 and metal contaminants 48 could affect CNT toxicity in vivo or in vitro. Comparing with f-MWCNT, more inflammation occurred in the p-MWCNTs.…”
Section: Physicochemical Characteristic Dependency Of Effects/relatiomentioning
confidence: 99%
“…With extensive biomedical applications, large variety of surface-modified CNTs should be systematically evaluated in toxic effects in vivo, especially in immunotoxicity. Furthermore, other factors influence the toxicity effects of MWCNTs and have the potential to modulate their biological effects, such as their sizes, 25 lengths, 26 and contamination with metal catalysts. 27 Several data indicate that length is one of the most important determinants for toxicity of CNTs and it is unclear whether the length of MWCNTs affects the outcome of immunotoxicity, which is one of the concerns in our study.…”
mentioning
confidence: 99%
“…While there is much ongoing effort for using CNTs in drug delivery and biomedical applications, it is worth noting that there have been concerns about the toxicity of CNTs and numerous in vitro and in vivo studies have been carried out with conflicting reports 4048 . However, functionalization with carboxyl group has shown to be an effective way to mitigate MWCNTs toxicity 4950 .…”
Section: Introductionmentioning
confidence: 99%
“…Anionic –COOH functionalization reduced epithelial, fibroblast, and macrophage cytotoxicity and inflammasome activation (Sayes et al, 2006), while strong cationic surfaces increased surface reactivity, resulting in strong inflammasome activation and fibrogenic potential (Li et al, 2013b). Other studies, however, found no difference between –COOH and –NH 2 functionalized MWCNT toxicity, since functional group presence caused increased protein binding and agglomeration (Allegri et al, 2016; Coccini et al, 2013). …”
Section: Discussionmentioning
confidence: 91%
“…To discern differences in the ability of various carbon ENMs ability to bind lung surfactant and protein that may impact toxicological response, each carbon ENM was incubated with Survanta lung surfactant in SAGM medium, analyzed by SDS Page gels, and bound protein quantified using previously described methods (Allegri et al, 2016). Stained protein bands on gels were imaged and quantified using FluoroChem SP.…”
Section: Methodsmentioning
confidence: 99%